ANALISIS TECNOLOGICAL KNOWLEDGE GURU GEOGRAFI DI KABUPATEN SOLOK SELATAN PROVINSI SUMATERA BARAT - Roki Arul Saputra; surtani surtani (JURNAL BUANA, 2020)
Abstract This study aims to determine the level of ability of Geography teachers in making and developing technology in learning and utilizing technology as a media for mapping, remote sensing and geographic information systems. The research method used in this research is quantitative descriptive method in the form of a percentage. Samples were obtained using the Total Sampling technique, which means that all teachers teaching geography at SMAN in South Solok totaled as many as 14 people. Data collection is done by giving questionnaires. Data analysis was performed using IBM SPSS version 19.0 program consisting of descriptive analysis, test data analysis requirements and descriptive analysis or percentage descriptive statistics. Based on the results of the study, it was concluded that the level of technological knowledge of Geography Teachers in 5 indicators, namely basic computer operating knowledge, use of number processing programs, word processing, teacher presentation programs, how to access the internet, and utilizing IT to help understand the concept of Geogarfi Teachers in teaching, is still relatively low with percentage of 57% Keyword: knowledge, technology, geography teacher ability Abstract This study aims to determine the level of ability of Geography teachers in making and developing technology in learning and utilizing technology as a media for mapping, remote sensing and geographic information systems. The research method used in this research is quantitative descriptive method in the form of a percentage. Samples were obtained using the Total Sampling technique, which means that all teachers teaching geography at SMAN in South Solok totaled as many as 14 people. Data collection is done by giving questionnaires. Data analysis was performed using IBM SPSS version 19.0 program consisting of descriptive analysis, test data analysis requirements and descriptive analysis or percentage descriptive statistics. Based on the results of the study, it was concluded that the level of technological knowledge of Geography Teachers in 5 indicators, namely basic computer operating knowledge, use of number processing programs, word processing, teacher presentation programs, how to access the internet, and utilizing IT to help understand the concept of Geogarfi Teachers in teaching, is still relatively low with percentage of 57% Keyword: knowledge, technology, geography teacher ability